A qualitative assessment tool to measure appropriation of ICT's [Herramienta de evaluación cualitativa para valorar apropiación de las TIC] (2017)
Postmodernism has brought about a hyper-valuation of the use of ICT, often leaving aside the impact that these have in shaping a more egalitarian society. Aware of the importance of this issue, we offer to the academic community this article that gathers, succinctly, the main results obtained after the application of a qualitative assessment tool to an ICT project in a learning community. This tool is the result of a more than three-year-long research process, which included the design of the theoretically supported model and its application via a pilot test. This paper describes the aforementioned research process, starting from the theoretical and methodological justification of the need to generate this ICT evaluation tool that goes beyond the quantitative, going through the development tool itself, to its application in a project of digital inclusion sponsored by Telefónica Foundation. It also discusses the reasons within the communicative perspective that justify it, its most relevant results and, finally, the possibilities offered by said Assessment Tool. © 2017 (María Cristina Pinto Arboleda & Nora Elena Botero).